Plant abiotic stress signaling - Akpinar, B. Ani (Landes Bioscience, 2012)
Stress signaling is central to plants which—as immobile organisms—have to endure environmental fluctuations that constantly interfere with vigorous growth. As a result, plant-specific, elaborate mechanisms have evolved to perceive and respond to stress conditions. Currently, these stress responses are plausibly being revealed to involve crosstalks with energy signaling pathways as any growth-limiting factor alters plant’s energy status. Among these, autophagy, conventionally regarded as the mechanism whereby plants recycle and remobilize nutrients in bulk, has frequently been associated with stress responses. With the recent discoveries, however, autophagy has attained a novel role in stress signaling. In this review, major elements of abitoic stress signaling are summarized along with autophagy pathway, and in the light of recent discoveries, a putative, state-of-art role of autophagy is discussed.